Pengaruh Gaya Kepemimpinan Dan Budaya Organisasi Terhadap Kinerja Karyawan PT. PLN (Persero) Wilayah Papua Dan Papua Barat Area Manokwari - Marzellina E. Rumbekwan; Yulius H. Saptomo; Margareth S. Sabarofek (Pusat Penelitian Pemberdayaan Fiskal dan Ekonomi Daerah (P3FED) Universitas Papua, 2019)
The purpose of this study was to determine the effect of leadership style and organizational culture on the performance of employees of PT PLN (Persero) Region of Papua and West Papua Manokwari Area. This research is an associative study using quantitative data. Data sources include primary data and secondary data. The population in this study were all employees of PT PLN (Persero) in the Papua and West Papua Areas of the Manokwari Area. The sampling method uses simple random sampling with the number of respondents 67 employees. Data were analyzed using simple linear regression. The results showed that, both partially (t test) and simultaneously (F test), leadership style and organizational culture had a significant effect on employee performance. Adjusted R Square value of 0.495 shows that 49.5% of the variation in the performance of employees of PT PLN (Persero) in the Papua and West Papua Areas of Manokwari is influenced by leadership style and organizational culture.